2019
DOI: 10.1002/wsb.992
|View full text |Cite
|
Sign up to set email alerts
|

Identifying predators from saliva at kill sites with limited remains

Abstract: Kill-site investigations can yield valuable data about elusive predators and predator-prey interactions, provided the predator species can be definitively identified as the one responsible for the predation event. The traditional method of visually analyzing prey remains to identify predators is prone to observer bias and may be particularly challenging when few remains are present or in systems with congeneric predators. Other potential evidence left by predators, such as scat, may be difficult to reliably li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 97 publications
(128 reference statements)
0
9
0
Order By: Relevance
“…It is reasonable to expect that snow could help preserve DNA while rain could wash it away which may explain the lack of a net effect from precipitation. Peelle et al (2019) found that amplification success of predator DNA from snowshoe hare kills was more successful when samples were collected from hard surfaces, such as the plastic collar box, compared to soft surfaces such as bite wounds. In contrast, we did not detect an effect of the swabbing surface on amplification success.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reasonable to expect that snow could help preserve DNA while rain could wash it away which may explain the lack of a net effect from precipitation. Peelle et al (2019) found that amplification success of predator DNA from snowshoe hare kills was more successful when samples were collected from hard surfaces, such as the plastic collar box, compared to soft surfaces such as bite wounds. In contrast, we did not detect an effect of the swabbing surface on amplification success.…”
Section: Discussionmentioning
confidence: 99%
“…We predicted that DNA collected from artificial surfaces (i.e. the collar and ear tags) would have higher rates of success in amplifying predator DNA (Peelle et al 2019), and we expected that samples of predator DNA collected from the carcasses of larger prey (i.e., adult deer versus elk calves and deer fawns) would also be more successful in providing genetic information because the predator may spend more time handling and feeding on large prey, depositing more saliva.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Technology that can support predation data from telemetry will continue to develop, including such techniques as eDNA to swab recovered tags and more molecular methods for prey biopsies to understand genotypes and phenotypes of prey and how these relate to selection (Miller et al 2014, Peelle et al 2019). The development of more specific genetic markers and utilization of new types of PCR methods such as droplets digital PCR (Allan et al 2021) methods will enable scientists to generate increasingly accurate links between prey and predators from non‐invasive material such as saliva (Peelle et al 2019).…”
Section: Horizon Scanning Predation Research With Telemetrymentioning
confidence: 99%
“…Technology that can support predation data from telemetry will continue to develop, including such techniques as eDNA to swab recovered tags and more molecular methods for prey biopsies to understand genotypes and phenotypes of prey and how these relate to selection (Miller et al 2014, Peelle et al 2019). The development of more specific genetic markers and utilization of new types of PCR methods such as droplets digital PCR (Allan et al 2021) methods will enable scientists to generate increasingly accurate links between prey and predators from non‐invasive material such as saliva (Peelle et al 2019). In parallel, identification of genetic markers that allow analysts to identify physiological state based on small biopsies will allow analysts to couple predation events with physiological state, facilitating insights into how compensatory or additive mortality operates within populations of prey as tagged animals are progressively determined to succumb to predation.…”
Section: Horizon Scanning Predation Research With Telemetrymentioning
confidence: 99%